2021
DOI: 10.1101/2021.04.29.441713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular adenosine induces hypersecretion of IL-17A by T-helper 17 cells through the adenosine A2a receptor to promote neutrophilic inflammation

Abstract: Extracellular adenosine, produced from ATP secreted by neuronal or immune cells, may play a role in endogenous regulation of inflammatory responses. However, the underlying molecular mechanisms are largely unknown. Here, we show that adenosine primes hypersecretion of interleukin (IL)-17A by CD4+ T cells via T cell receptor activation. This hypersecretion was also induced by an adenosine A2a receptor (A2aR) agonist, PSB0777. In addition, an A2aR antagonist, Istradefylline, and inhibitors of adenylcyclase and p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, we reported that adenosine is produced by activated CD4 + T cells, and primes hypersecretion of IL-17A by CD4 + T cells through A2aR. 38 These results suggest that CD39 and CD73 expressed on the CD4 + T cell surface converts ATP to adenosine, and adenosine binds to A2aR and primes hypersecretion of IL-17A (Figure 5). Some researchers argue that an A2aR agonist, CGS21680, suppresses Th17 differentiation.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Furthermore, we reported that adenosine is produced by activated CD4 + T cells, and primes hypersecretion of IL-17A by CD4 + T cells through A2aR. 38 These results suggest that CD39 and CD73 expressed on the CD4 + T cell surface converts ATP to adenosine, and adenosine binds to A2aR and primes hypersecretion of IL-17A (Figure 5). Some researchers argue that an A2aR agonist, CGS21680, suppresses Th17 differentiation.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, ARL67156 and AMP-CP, which inhibit the production of adenosine, suppressed IL-17-dependent neutrophilic airway inflammation, which corroborates our previous findings. 38 [51][52][53][54] In recent previous studies, patients with severe COVID-19 showed the aberrant activation of neutrophils and Th17 promotion, 55 and IL-17 can serve as a biomarker of the severity of COVID-19. 56 Indeed, autopsy samples from the lungs of COVID-19 patients showed neutrophil infiltration in pulmonary capillaries, 57 and the peripheral blood of patients showed an increased frequency of Th17 cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations